Differential Molecular Diffusion in a Hydrogen-Rich Jet. (January 2016) - Sannan, Sigurd; Kerstein, Alan R.
Abstract: Differential molecular diffusion effects are expected to be of particular importance in the combustion of hydrogen and H2 -enriched fuels. The mixing between fuel and oxidizer can be significantly influenced, implying changed chemical reaction rates and overall heat release. Here, the LEM3D model based on the Linear Eddy Model (LEM) is employed to simulate differential diffusion effects in a turbulent round jet of H2 and Freon 22 issuing into air. Input to LEM3D, generated from ANSYS Fluent, consists of velocity profiles and profiles for the turbulent diffusivity, the Kolmogorov scale and the integral length scale. In this paper, the LEM3D-Fluent coupling is demonstrated by a coarse steady-state RANS simulation in Fluent with a one-to-one correspondence between the RANS grid cells and the LEM3D control volumes. The LEM3D simulation results are compared with previously obtained measurements of differential molecular diffusion for the given flow configuration.